미국의 복지개혁과 농촌복지 - 박대식 (한국농촌경제연구원, 2008)
The main purposes of this study are as follows: 1) to identify the welfare reform trend of the U.S.; 2) to analyze the rural impact of the welfare reform; 3) to suggest some policy implications to improve the rural welfare in Korea. The major research methods include the collection and analysis of existing data, interview, and so on. Existing related data were collected by searching the data of related research institutes and governmental organizations. The Personal Responsibility and Work Opportunity Act of 1996(PRWORA) dramatically transformed the federal safety net and the food assistance landscape for low-income households in the United States. PRWORA changed the program from an entitlement to a block grant, stiffened work and child support requirements, limited families to five years of aid, denied coverage to many non-citizens, and gave states more control over welfare. PRWORA replaced the entitlement program Aid to Families with Dependent Children(AFDC) with the Temporary Assistance to Needy Families(TANF) program, which is funded through block grants to states. Although various research has focused on understanding how these reforms are affecting the lives of low-income families, most research has focused on urban areas. TANF emphasizes moving from welfare to work by imposing a five-year lifetime limit on receiving federal welfare benefits, requiring recipients to participate in work activities within two years of receiving benefits, and penalizing states that have too few recipients in work activities by reducing the federal contribution to their TANF funds. Results from recent national and state-level studies of rural welfare reform are mixed. At the national level, welfare reform outcomes did not differ greatly between rural and urban areas, and were successful. Assessment of the effects of welfare reform in rural areas, however, is complicated by the increased variation among state programs. State programs differ, for example, on sanctions imposed for noncompliance, the amounts and types of assets that are used in determining eligibility and benefits, the time period for work requirements, and the design of child care and transportation assistance programs. When national level findings are dis-aggregated by State and by rural and urban areas within states, a less positive picture emerges for some rural places, particularly the poorest and most remote rural areas. Researcher: Dae Shik Park(Ph.D.) E-mail: pds8382@krei.re.kr